The synthesis of novel, unsymmetrically substituted, chiral naphthalene and perylene diimides: Photophysical, electrochemical, chiroptical and intramolecular charge transfer properties - Asir, Suleyman; Demir, Ayhan S.; Icil, Huriye (Elsevier Sci Ltd, 2010)
A novel naphthalene monoimide and two unsymmetric chiral chimides (naphthalene and perylene) were synthesized; for comparison purposes, the perylene monoimide with the same substituent in the naphthalene monoimide was prepared. The naphthalene monoimide exhibited intramolecular charge transfer complexation in polar solvents. Excimer-like emissions were obtained in non-polar, polar protic and aprotic solvents in the cases of both the naphthalene monoimide and diimide. The specific optical rotation values of unsymmetrical chiral naphthalene and perylene diimides were -221.6 and -24, respectively at 20 degrees C The Chiral naphthalene diimide showed prominent, negative Cotton effects centred at 362 and 382 nm in CH3CN. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Unsymmetrical naphthalene diimides; Unsymmetrical perylene diimides; Chirality; Charge transfer; Exciplex; Cyclic voltammetry